The AI Dietitian: Can Artificial Intelligence Provide Reliable Nutrition Advice? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into daily life has been rapid and transformative, leading to an inevitable question in the realm of health: Ca...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Wearable Technology; Medical Ethics